2015
DOI: 10.1089/dia.2014.0259
|View full text |Cite
|
Sign up to set email alerts
|

Multinight “Bedside” Closed-Loop Control for Patients with Type 1 Diabetes

Abstract: Background: Studies of closed-loop control (CLC) systems have improved glucose levels in patients with type 1 diabetes. In this study we test a new CLC concept aiming to ''reset'' the patient overnight to nearnormoglycemia each morning, for several consecutive nights. Subjects and Methods: Ten insulin pump users with type 1 diabetes (mean age, 46.4 -8.5 years) were enrolled in a two-center (in the United States and Italy) randomized crossover trial comparing 5 consecutive nights of CLC (23:00-07:00 h) in an ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 17 publications
(20 reference statements)
1
29
0
2
Order By: Relevance
“…This pathway included several feasibility and safety trials in hotel settings (8,12,13), summer camp studies testing DiAs in children with diabetes (14,15), and the recently completed overnight (16) and 42-h dinner-overnight (17) trials of CLC at home. Here, we describe the first longer-term use of DiAs–USS Virginia at home using a completely wireless and portable, wearable AP system.…”
Section: Introductionmentioning
confidence: 99%
“…This pathway included several feasibility and safety trials in hotel settings (8,12,13), summer camp studies testing DiAs in children with diabetes (14,15), and the recently completed overnight (16) and 42-h dinner-overnight (17) trials of CLC at home. Here, we describe the first longer-term use of DiAs–USS Virginia at home using a completely wireless and portable, wearable AP system.…”
Section: Introductionmentioning
confidence: 99%
“…In general, these systems use feedback from continuous glucose sensors to inform insulin delivery based upon current glucose values, rate of change, and various prediction models. Several approaches have demonstrated the feasibility of feedback-based insulin modulation, and advances in both sensor performance and algorithms have demonstrated a reduction in hypoglycemia, glucose variability, and decreased mean glucose levels in controlled inpatient settings (15) as well as outpatient studies (613) extending to 12 weeks of use in the home setting (14). …”
Section: Introductionmentioning
confidence: 99%
“…10 It was also shown that real-time CGM reduced significantly severe hypoglycemia while improving hemoglobin A1c in patients with established hypoglycemia unawareness. 11 Moreover, virtually all contemporary studies of threshold 12 or predictive 13 low glucose suspend and closedloop control (known as the artificial pancreas) [14][15][16][17][18] report significant reduction of hypoglycemia achieved by real-time control algorithms using CGM data as their principal source of information. Thus, CGM data contain valuable information that, if sufficiently accurate and correctly interpreted by the patient or by automated algorithms, can help with optimization of diabetes control and with reducing the risk for hypoglycemia.…”
Section: The Optimization Problem Of Diabetesmentioning
confidence: 99%